Analisis Faktor-Faktor Yang Mempengaruhi Manajemen Laba (Studi Empiris Pada Perusahaan Sektor Property And Real Estate Yang Terdaftar Di Bei Periode 2016-2020) - Baitika Ayu Lestari; Dirvi Surya Abbas (LPPM Universitas Putera Batam, 2022)
The purpose of this study is to analyze the factors that influence earnings management in real estate and property sub-sector companies listed on the Indonesia Stock Exchange (IDX). The research time period used is 5 years, namely the 2016-2020 period. The design of this study uses an explanatory causality design with path analysis. The population of this study includes all property and real estate companies listed on the Indonesia Stock Exchange (IDX) for the 2016-2020 period. The sampling technique used was purposive sampling technique. Based on the predetermined criteria obtained 10 companies. The type of data used is secondary data obtained from the Indonesia Stock Exchange website. The results showed that: (1) managerial ownership (KM) had no effect on earnings management with a t-count value of 1.363 and sig 1 tailed 0.182: 2 = 0.091. (2) Profitability (ROA) has a positive and significant effect on earnings management with a t value of 3.287 and a value of sig 1 tailed 0.002 : 2 = 0.001 and has a positive beta value. (3) Leverage (DER) has a positive and significant effect on earnings management with a t-count value of 2.316 and a value because of sig 1 tailed 0.027: 2 = 0.0135 and has a positive beta value. (4) Firm size (SIZE) has a negative effect on earnings management with a t value of 1.817 and a value of sig 1 tailed 0.078 : 2 = 0.039 and has a negative beta value